2015
DOI: 10.17679/iuefd.16101104
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Ders Çalışma Alışkanlıkları

Abstract: Abstract:In this study, the relationship between the students '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…Arslantaş (2001) stated that students had "moderately" efficient study habits and Yiğit (2014) stated that they had highly efficient study habits, whereas Brown (1941), Barrilleaux (1972), Küçükahmet (1987), Tümkaya and Bal (2006), Mendezabal (2013), and Lalrintluangi (2018) stated in their studies that the participants did not have an appropriate and expected study habits and attitudes. Tulum (2001) concluded that the scores for the study habits of the nursing students were higher than their study attitudes, whereas Durukan et al (2015) concluded that the prospective teachers had low study habits. In the study conducted by Rana and Kausar (2011) with Pakistani and British students of 10 th grade between the ages of 14-16, it was stated that the study habits of the British students were significantly higher than the Pakistani students and there was no significant difference between their academic performances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arslantaş (2001) stated that students had "moderately" efficient study habits and Yiğit (2014) stated that they had highly efficient study habits, whereas Brown (1941), Barrilleaux (1972), Küçükahmet (1987), Tümkaya and Bal (2006), Mendezabal (2013), and Lalrintluangi (2018) stated in their studies that the participants did not have an appropriate and expected study habits and attitudes. Tulum (2001) concluded that the scores for the study habits of the nursing students were higher than their study attitudes, whereas Durukan et al (2015) concluded that the prospective teachers had low study habits. In the study conducted by Rana and Kausar (2011) with Pakistani and British students of 10 th grade between the ages of 14-16, it was stated that the study habits of the British students were significantly higher than the Pakistani students and there was no significant difference between their academic performances.…”
Section: Discussionmentioning
confidence: 99%
“…Memiş (2013) stated that Turkish course achievement was the predictor of the study habits and attitudes of the male students. Similar to the study, Ahmann and Glock (1957), Cavanaugh (1982), Koivo (1982), Gonzales (1984), Clark-Thayer (1987), Snodgrass (1989), Wonnacott (1989), Yeh (1990), Agnew et al (1993), Blumner and Richards (1997), Al-Hilawani and Sartawi (1997), Carter (1999), Okpala et al (2000), Gettinger and Seibert (2002), Yip and Chung (2005), Akagah (2011), Singh (2011), Demir et al (2012), Memiş (2013), Durukan et al (2015), Del Villar et al (2016), Kızılboğa (2017), Nandhini (2017), Numan and Syeda (2017), Sakirudeen and Sanni (2017), Bentil et al (2018), Lalrintluangi (2018) determined that the academic achievements of the students increased as the level of effective use of study methods. Murray and Wren (2003) stated that there was a low and significant relationship between only the sub-dimension of teacher approval and the academic average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tümkaya ve Bal (2006) yaptıkları çalışmada ders çalışma alışkanlıklarına sahip olan öğrencilerin daha başarılı olduğunu bulmuşlardır. Bununla birlikte Durukan, Batman ve Yiğit (2015) yaptıkları çalışmada öğretmen adaylarının ders çalışma alışkanlıkları ile akademik başarıları arasında anlamlı bir ilişki olduğunu bulmuşlardır. Küçükahmet (2000) ise öğrencilerin okul başarısızlıkları altında yatan en büyük nedenlerden birinin ders çalışma becerilerindeki yetersizlikler olduğunu ifade etmektedir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Durukan, Batman ve Yiğit, 2015). Yapılan araştırmalarda, öğrencilerin çalışma alışkanlıkları ile akademik başarıları arasında pozitif yönde anlamlı ilişkiler bulunmuştur (Durukan, Batman ve Yiğit, 2015;Nonis, & Hudson, 2010;Onwuegbuize, Slate & Schwartz, 2001;Karapınar, 2000;Yip & Chung, 2002 …”
Section: Introductionunclassified